From the principles of genomic data sharing to the practices of data access committees. Issue 5 (10th March 2015) - Shabani, Mahsa; Knoppers, Bartha Maria; Borry, Pascal
<x xml:space="preserve">Abstract</x> Sharing genomic research data through controlled‐access databases has increased in recent years. Policymakers and funding organizations endorse genomic data sharing in order to optimize the use of public funds and to increase the statistical power of databases. Well‐established data access arrangements and data access committees (DACs)—responsible for reviewing and managing requests for access to genomic databases—are therefore central for implementing the policies and principles of data sharing. This article aims to investigate the functionality of DACs through the perspective of existing practices.